Justification and development of a continuous deflector with full core sampling for drilling exploration wells - Pavel A. Blinov; Nikita M. Silichev; Vyacheslav V. Nikishin; Vladimir G. Gorelikov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2025)
Relevance. Exploration of new mineral deposits is associated with high costs of geological exploration works. The main way to obtain information on the concentration of mineral components in solid mineral deposits is still drilling exploration wells with coring. Consequently, the most promising way to reduce costs is to reduce drilling of overlying non-metallic rocks. This cost reduction can be achieved by optimizing exploration grids with directional and multilateral wells using continuous diverters. Aim. To analyze the main advantages of multilateral and directional drilling, as well as identify the factors limiting their widespread introduction into exploration practice. To systematize data on existing technical solutions in the field of directional drilling, assessing their efficiency and key drawbacks. To formulate a set of requirements to the design of a continuous deflector oriented to improve the accuracy and productivity of exploration drilling. Methods. Solid modeling, mathematical modeling. Results and conclusions. An effective technology for solving this problem is the creation of a continuous defector for drilling with coring. The paper presents a device realizing the mechanism of curvature similar to those used in rotary steerable systems “point the bit” – bending of quill drive shaft inside eccentric rings. The authors defined the basic requirements for successful operation of a defector in a well. As a result, they developed a new design of continuous defector for drilling diameter N (76 mm) taking into account all the requirements put forward. In further research it is planned to develop a mathematical model of the drive shaft bending and to transfer from the bending value (eccentric bushing rotation) to the intensity of the borehole curvature.